PERANCANGAN SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA SMA N 14 MUARO JAMBI - Ahmad Farianto; Yudi Novianto; Martono Martono (LPPM STIKOM Dinamika Bangsa, 2014)
In the process of data processing in SMA N 14 Muaro Jambi, administrative staff are still using paper recording, so it takes a long time in terms of search and report generation. Purpose of this study was to analyze problems that occur on academic information system that is currently running at the SMA N 14 Muaro Jambi. Other than i also want to design a system that is web-based academic information that will be used as a tool running system today. The method used in this research is the waterfall method and system modeling is object-oriented modeling is by using tools such as system design use case diagram, activity diagram, class diagram, and flowchart. This research resulted in applications that facilitate the school in improving performance in data processing and provision of report required by the school. With this application can help the school in its vision of making SMA N 14 Muaro Jambi into quality schools. Keywords: Information System, Web, Academic